The Body as Evidence for the Nature of Language - Sandler, Wendy (Frontiers in Psychology, 2018)
Taking its cue from sign languages, this paper proposes that the recruitment and composition of body actions provide evidence for key properties of language and its emergence. Adopting the view that compositionality is the fundamental organizing property of language, we show first that actions of the hands, face, head, and torso in sign languages directly reflect linguistic components, and illuminate certain aspects of compositional organization among them that are relevant for all languages, signed and spoken. Studies of emerging sign languages strengthen the approach by showing that the gradual recruitment of bodily articulators for linguistic functions directly maps the way in which a new language increases in complexity and efficiency over time. While compositional communication is almost exclusively restricted to humans, it is not restricted to language. In the spontaneous, intense emotional displays of athletes, different emotional states are correlated with actions of particular face and body features and feature groupings. These findings indicate a much more ancient communicative compositional capacity, and support a paradigm that includes visible body actions in the quest for core linguistic properties and their origins.